2018
DOI: 10.2147/jpr.s164303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pulsed electromagnetic field therapy for the treatment of chronic postoperative pain following lumbar surgery: a pilot, double-blind, randomized, sham-controlled clinical trial

Abstract: BackgroundThe incidence of chronic postoperative pain following lumbar spinal surgery has increased with the overall increase in the prevalence of lumbar surgery. This study was conducted to evaluate the analgesic effectiveness of pulsed electromagnetic field (PEMF) therapy in subjects with persistent pain following lumbar surgery.Patients and methodsA randomized, double-blind, sham-controlled, multicenter study in 36 subjects with persistent low-back and/or radiating leg pain after lumbar surgery was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…To date, PLIF is considered to be the optimal procedure due to its high fusion rate and effective decompression of neural roots [3]. However, some patients complain about new onset or persistent low back pain after PLIF surgery, known as "persistent low back pain" (PLBP) or "failed back surgery syndrome" (FBSS) [4]. Unfortunately, there is for sure no one exact cause for PLBP.…”
Section: Introductionmentioning
confidence: 99%
“…To date, PLIF is considered to be the optimal procedure due to its high fusion rate and effective decompression of neural roots [3]. However, some patients complain about new onset or persistent low back pain after PLIF surgery, known as "persistent low back pain" (PLBP) or "failed back surgery syndrome" (FBSS) [4]. Unfortunately, there is for sure no one exact cause for PLBP.…”
Section: Introductionmentioning
confidence: 99%
“…In 1979, the U.S. Food and Drug Administration (FDA) approved PEMF as safe and effective to treat delayed and non-unions in bone [12]. Since then, PEMF has been proposed to be effective in treating a variety of pathologies, including delayed wound healing [13], chronic postoperative pain [14], and osteoarthritis [15,16]. In vitro, PEMF has been shown to be potent in limiting the catabolic effects of pro-inflammatory cytokines on hyaline cartilage [17,18], suggesting that PEMF is able to limit inflammation and promote soft tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…PEMF is a noninvasive and safe treatment that commonly used in clinic to treat a variety of diseases/injuries including nonhealing fractures, postoperative pain, that edema, and osteoarthritis [13,14]. Li et al reported that electromagnetic fields are beneficial for relieving pain in patients with OA [15].…”
Section: Introductionmentioning
confidence: 99%